THE ELDERLY CARE, ACTIVE AGEING AND GERAGOGY: COULD THEY CO-EXIST IN UKRAINE AND HOW? - Semigina, Tetyana; Karkach, Andrii (Publishing house «UKRLOGOS Group», 2021)
Ukraine belongs to ‘greying’ nations and has one of the worst health profiles in the European region, characterized by high mortality, morbidity, and disability rates. In early 1990s, the country had in-herited the Soviet paternalistic model of social welfare with no professional social workers. Since that time the new services for elderly people have been gradually introduced. Looking through lenses of a number of theoretical concepts (the institutional framework, concept of dependency and geragogy theory) the chapter reviews the key features of the Ukrainian model of elderly care built up in 1990-2020 and the peculiarities of modern social work with elderly people. It reflects the country’s controversial experience of balancing the indigenous social patterns of paternalism, famial-istic informal care, marketization of social services, and professionalization of social work. The case of the municipal social service for elderly persons operating in Poltava region is presented. The spe-cial focus is made on specific interventions implemented in order to encourage older people to use computer and information technology in their daily lives, and to overcome digital inequalities in today’s information and network society. The educational activities for elderly people undertaken in this centre within the University of Third Age were evaluated.